DEVELOPMENT OF E-LKPD BASED (R2L) TO IMPROVE STUDENTSâ€™ HOTS SCIENCE LITERACY SKILLS - Kurnia Wati Br Bangun; Iis Siti Jahro (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Science literacy is the one very important skill that students must have. Students' ability to read is still classified as low. This reflects that level of higher-order thinking skills (HOTS) in scientific literacy has not been adequately developed. This research used kinds of development known as R&D (Research and Development) research. The product developed that is Interactive E-LKPD based on the R2L method on chemical equilibrium material. The result of need analysis that has been carried out state requires Interactive E-LKPD based on Reading to Learn (R2L) on chemical equilibrium material to increase HOTS Literacy students get data 100% students agree that using the interactive E-LKPD based on Reading to Learn (R2L) to be developed as a learning support. It was found that very feasible to used Sig <0.05, therefore Ha is accepted and H0 is rejected. Result give an interactive influence of E-LKPD based on Reading to Learn (R2L) on chemical equilibrium material on student learning outcomes and shows a increase in students' HOTS Science Literacy abilities also E-LKPD suitable to used.Â Keywords: Interactive E-LKPD, HOTS Ability, Literacy, R2L